The Impact of the Existence of the Seaweed Industry on the Socio-Economic Conditions of the Community in Suppa District, Pinrang Regency - Hamzah Tahang; Abdul Wahid; Irjayandi Irjayandi (ECSOFiM (Economic and Social of Fisheries and Marine Journal), 2022)
This research has the aim of knowing the public's perception of the existence of the seaweed industry, describe social and economic changes before and after the seaweed industry, and the impact on the community on the existence of the seaweed industry. The research was carried out in April-June 2019 in Suppa District, Pinrang Regency. This type of research uses a survey research type taking samples from the research population. Sampling using simple random sampling with a sample of 30 people. Data was collected through direct interviews and questionnaires to a number of selected respondents. The data analysis used is descriptive qualitative and quantitative data analysis. The results of this study indicate a positive response from the community about the existence of a seaweed industry built in their area. As many as 50% of the community stated that they strongly agreed with the existence of the seaweed industry and 67% of the local community expressed their interest in registering as workers in the seaweed industry. The existence of the seaweed industry can reduce the unemployment rate in Suppa District, Pinrang Regency. In addition, negative impacts also occur such as land disputes, pollution and also waste from the seaweed industry.